2011
DOI: 10.1111/j.1462-5822.2011.01722.x
|View full text |Cite
|
Sign up to set email alerts
|

Human heat shock protein (Hsp) 90 interferes with Neisseria meningitidis adhesin A (NadA)-mediated adhesion and invasion

Abstract: SummaryNadA (Neisseria meningitidis adhesin A), a meningococcal surface protein, mediates adhesion to and invasion of human cells, an activity in which host membrane proteins have been implicated. While investigating these host factors in human epithelial cells by affinity chromatography, we discovered an unanticipated interaction of NadA with heat shock protein (Hsp) 90, a molecular chaperone. The specific in vitro interaction of recombinant soluble NadA and Hsp90 was confirmed by co-immunoprecipitations, dot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 69 publications
(125 reference statements)
1
33
0
Order By: Relevance
“…Cell surface expression of HSP90 has been implicated in cancer invasion (31), autoimmunity (32), bacteria adhesion (33), and LPS signaling (34). However, the mechanism by which cell surface HSP90 exerts its function in these biological processes remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface expression of HSP90 has been implicated in cancer invasion (31), autoimmunity (32), bacteria adhesion (33), and LPS signaling (34). However, the mechanism by which cell surface HSP90 exerts its function in these biological processes remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that NadA is involved in interaction with and stimulation of immune cells during infection (2)(3)(4) and in binding to the human chaperone Hsp90 (5,6). Its predicted molecular structure is very similar to the known virulence-associated factors Yersinia adhesin A (YadA) and UspA2 (7,8), which suggests that NadA is a member of the OCA (oligomeric coiled-coil adhesin) family (9).…”
mentioning
confidence: 99%
“…This adhesive activity has been mapped, at least partially, to an N-terminal region extending to residue T132 (23,24). Recently, interactions of NadA3 with β-1 integrin (25) and with the heat shock protein Hsp90 (26) have been reported.…”
mentioning
confidence: 99%